Pain and Inflammation in Women With Early-Stage Breast Cancer Prior to Induction of Chemotherapy. (April 2013) - Starkweather, Angela R.; Lyon, Debra E.; Schubert, Christine M.
Context: Pain is a commonly experienced and distressing symptom in women with breast cancer (BCA), and recent evidence suggests that immune activation may be associated with pain and other co-occurring symptoms. However, no studies to date have explored the relationships among perceived pain and biomarkers of inflammation in women with early-stage BCA during the initial course of treatment. Objectives: The purpose of this research study was to examine the relationships among pro- and anti-inflammatory biomarkers and the presence of pain and other symptoms (anxiety, depression, fatigue, and sleep disorder) prior to induction of chemotherapy. Method: This was a secondary analysis of data that measured perceived symptoms, including the presence of pain and pain interference, and plasma levels of pro- and anti-inflammatory cytokines and C-reactive protein (CRP) in women with early-stage BCA ( N = 32) at 1 month postsurgery but prior to induction of chemotherapy. Results: Women experiencing pain had significantly higher levels of CRP ( p < .01), interleukin (IL) 13 ( p < .02), and IL-7 ( p < .02) and more pain interference ( p < .01), depression ( p < .01), and sleep disturbance ( p < .01) compared to women reporting no pain. Conclusion: The presence of pain during the initial course of treatment in women with early-stage BCA was associated with significantly higher levels of CRP, IL-7, and IL-13, suggesting a potential role of immune activation in perceived pain. Further research to examine the precise effects of these biological factors in modulating pain is needed. Perceived pain was also associated with multiple co-occurring symptoms, and this finding has important implications for symptom management.